Novye svedeniia o kontse sveta . Novye svedeniia o kontse sveta . New Information About the End of the World . Новые сведения о конце света - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The documentary discusses astrological, religious, and spiritual movements as well as their interpretations of the end of the world and the role of Vladimir Lenin in the approaching end of the world. Contributors: Kustov, Boris (Director) Астрология, религиозные и спиритические движения, их интерпретации конца света и роли Владимира Ленина в приближении конца света. Создатели: Кустов, Борис (Режиссер)